Vasiliou, Christina - (:unkn) unknown (My University, 2026)
Christina Vasiliou holds a Research Associate post within the department of Multimedia and Graphic Arts, where she is working on interactive tabletops and applications promoting collaboration. Christina has optained a Master's degree in Human Centred Interactive Technologies (with Dinstiction), from the University of York (2011) and a Bachelor degree in Computer Science, from the University of Cyprus(2010). Her research interests fall in the area of Human Computer Interaction, Interface Design, Interactive Touch Applications and Human Factors.
Keywords: arts